Universal newborn hearing screening online plattform on CHBV - Lopes, Ana Cristina (2017)
Introduction: Universal Newborn Hearing Screening is very important in the early detection and intervention of hearing loss. In this context, we aim to explain the benefits obtained with the protocol and with the platform's Hospital Baixo Vouga that objectify the improvement of functionality and quality of newborn hearing screening.Study design: Retrospective study.Methods: Newborns evaluated at CHBV in the neonatal hearing screening program in the period January to December 2014.Results: The protocol established allowed to get a hearing screening rate made 99.9%, and a false positive rate of 0.4% .The platform contains the information inherent to the newborns in every phase of hearing screening. In 2014, 1663 newbons were screened, of these were detected 5 cases (0,3%) with sensorineural hearing loss.Conclusion: The results allow us to conclude, that the hearing screening program implemented were in agreement to the standards suggested by GRISI.